L. pneumophila CMP-5, 7-di-N-acetyllegionaminic acid synthetase (LpCLS)-involved chemoenzymatic synthesis of sialosides and analogues. Issue 4 (8th January 2020) - McArthur, John B.; Santra, Abhishek; Li, Wanqing; Kooner, Anoopjit S.; Liu, Ziqi; Yu, Hai; Chen, Xi
Abstract : A bacterial CMP-5, 7-di- N -acetyllegionaminic acid synthetase was characterized and used in one-pot multienzyme systems for efficient synthesis of Leg5, 7Ac2 -glycosides and analogs. Abstract : 5, 7-Di- N -acetyllegionaminic acid (Leg5, 7Ac2 ) is a bacterial nonulosonic acid (NulO) analogue of sialic acids, an important class of monosaccharides in mammals and in some bacteria. To develop efficient one-pot multienzyme (OPME) glycosylation systems for synthesizing Leg5, 7Ac2 -glycosides, Legionella pneumophila cytidine 5′-monophosphate (CMP)-Leg5, 7Ac2 synthetase (LpCLS) was cloned and characterized. It was successfully used in producing Leg5, 7Ac2 -glycosides from chemoenzymatically synthesized Leg5, 7Ac2 using a one-pot two-enzyme system or from its chemically synthesized six-carbon monosaccharide precursor 2, 4-diacetamido-2, 4, 6-trideoxymannose (6deoxyMan2, 4diNAc) in a one-pot three-enzyme system. In addition, LpCLS was shown to tolerate Neu5Ac7NAc, a C9-hydroxyl analogue of Leg5, 7Ac2 and also a stable analogue of 7- O -acetylneuraminic acid (Neu5, 7Ac2 ), to allow OPME synthesis of the corresponding α2–3-linked sialosides, from chemically synthesized six-carbon monosaccharide precursor 4- N -acetyl-4-deoxy- N -acetylmannosamine (ManNAc7NAc).